I soffitti di palazzo Farnese a Roma: tradizione e innovazione - D’Amelio, Maria Grazia (Opus Incertum, 2018)
Between 1545 and 1625, twenty-five wooden ceilings were executed in Palazzo Farnese, in Rome, not to mention the ones lost due to collapses or in the fires of 1612, 1615 and 1701. The inventory is much broader than in any other private palace of Rome, and helps to understand the change in taste that, reflected in the form of this constructive element, suggests the transformation of Roman residential architecture in the sixteenth century. Palazzo Farnese is a living laboratory where old-fashioned ceilings with ’unlimited’ extension, still linked to a system based on wooden beams, and those of original creation become essential models for the architecture of Modern Rome and of Europe at large.